Transcriptome-wide analysis reveals gluten-induced suppression of small intestine development in young chickens - Kang, Darae; Shin, Donghyun; Choe, Hosung; Hwang, Doyon; Bugenyi, Andrew Wange; Lee, Hak-Kyo; Heo, Jaeyoung; Shim, Kwanseob (Journal of animal science and technology, 2022)
Wheat gluten is an increasingly common ingredient in poultry diets but its impact on the small intestine in chicken is not fully understood. This study aimed to identify effects of high-gluten diets on chicken small intestines and the variation of their associated transcriptional responses by age. A total of 120 broilers (Ross Strain) were used to perform two animal experiments consisting of two gluten inclusion levels (0% or 25%) by bird's age (1 week or 4 weeks). Transcriptomics and histochemical techniques were employed to study the effect of gluten on their duodenal mucosa using randomly selected 12 broilers (3 chicks per group). A reduction in feed intake and body weight gain was found in the broilers fed a high-gluten containing diet at both ages. Histochemical photomicrographs showed a reduced villus height to crypt depth ratio in the duodenum of gluten-fed broilers at 1 week. We found mainly a significant effect on the gene expression of duodenal mucosa in gluten-fed broilers at 1 week (289 differentially expressed genes [DEGs]). Pathway analyses revealed that the significant DEGs were mainly involved in ribosome, oxidative phosphorylation, and peroxisome proliferator-activated receptor (PPAR) signaling pathways. These pathways are involved in ribosome protein biogenesis, oxidative phosphorylation and fatty acid metabolism, respectively. Our results suggest a pattern of differential gene expression in these pathways that can be linked to chronic inflammation, suppression of cell proliferation, cell cycle arrest and apoptosis. And via such a mode of action, high-gluten inclusion levels in poultry diets could lead to the observed retardation of villi development in the duodenal mucosa of young broiler chicken.Wheat gluten is an increasingly common ingredient in poultry diets but its impact on the small intestine in chicken is not fully understood. This study aimed to identify effects of high-gluten diets on chicken small intestines and the variation of their associated transcriptional responses by age. A total of 120 broilers (Ross Strain) were used to perform two animal experiments consisting of two gluten inclusion levels (0% or 25%) by bird's age (1 week or 4 weeks). Transcriptomics and histochemical techniques were employed to study the effect of gluten on their duodenal mucosa using randomly selected 12 broilers (3 chicks per group). A reduction in feed intake and body weight gain was found in the broilers fed a high-gluten containing diet at both ages. Histochemical photomicrographs showed a reduced villus height to crypt depth ratio in the duodenum of gluten-fed broilers at 1 week. We found mainly a significant effect on the gene expression of duodenal mucosa in gluten-fed broilers at 1 week (289 differentially expressed genes [DEGs]). Pathway analyses revealed that the significant DEGs were mainly involved in ribosome, oxidative phosphorylation, and peroxisome proliferator-activated receptor (PPAR) signaling pathways. These pathways are involved in ribosome protein biogenesis, oxidative phosphorylation and fatty acid metabolism, respectively. Our results suggest a pattern of differential gene expression in these pathways that can be linked to chronic inflammation, suppression of cell proliferation, cell cycle arrest and apoptosis. And via such a mode of action, high-gluten inclusion levels in poultry diets could lead to the observed retardation of villi development in the duodenal mucosa of young broiler chicken.